Enhancing dielectric properties of barium titanate macrofibers. Issue 13 (October 2019) - Sebastian, T.; Michalek, A.; Hedayati, M.; Lusiola, T.; Clemens, F.
Abstract: The motivation of this work was to improve the dielectric properties of BaTiO3 (BT) macrofibers by mixing BT nanofibers and commercial BT powder. BT nanofibers were fabricated via electrospinning synthesis. The calcined electrospun nanofibers were chopped and mixed with BT powder and converted in to a thermoplastic feedstock for extrusion of ceramic macrofibers with a diameter of 500 μm. The electromechanical properties of the BaTiO3 macrofibers were investigated by varying calcination temperature of the nanofibers. For both nano and macro fibers, microstructure and phase composition was investigated by SEM and XRD. It could be observed that an increase in calcination temperature of the nanofibers enhanced the final electromechanical properties of the sintered macrofibers. The relative permittivity increased almost twice, the remanent polarisation increased about 4 times and the strain almost increased 10 times with the addition of calcined nanofibers to macrofibers.